2015
DOI: 10.1007/s00595-015-1182-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic cholecystectomy versus traditional laparoscopic cholecystectomy performed by a single surgeon: findings of a randomized trial

Abstract: We found SILC to be a safe, feasible, and adaptable surgical technique. The pain scores at 4 h were significantly better for SILC than for TLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…This high detectability of the running course of the cystic duct after dissection in Calot's triangle (100 %) was similar to that reported previously (range 71.4-100 %) [1][2][3][4]. When fluorescent cholangiography identified biliary structures before dissection in Calot's triangle, fluorescent cholangiography could prevent biliary injury during SILC; however, meticulous maneuver without dependence on the findings of fluorescent cholangiography is imperative for preventing biliary injury when dissecting in Calot's triangle to obtain the so-called "critical view of safety" during SILC [7,8,[10][11][12].…”
Section: Discussionsupporting
confidence: 83%
“…This high detectability of the running course of the cystic duct after dissection in Calot's triangle (100 %) was similar to that reported previously (range 71.4-100 %) [1][2][3][4]. When fluorescent cholangiography identified biliary structures before dissection in Calot's triangle, fluorescent cholangiography could prevent biliary injury during SILC; however, meticulous maneuver without dependence on the findings of fluorescent cholangiography is imperative for preventing biliary injury when dissecting in Calot's triangle to obtain the so-called "critical view of safety" during SILC [7,8,[10][11][12].…”
Section: Discussionsupporting
confidence: 83%
“…The mean surgical time observed was approximately 68 min and is within the mean found in the literature for MPLS and single port cholecystectomies, evidencing that the single port operation did not cause any impairment in relation to anesthetic time, increase of drugs used, longer time on surgery room and greater risk associated to the surgical time 1 , 3 , 4 , 11 , 13 , 16 , 18 , 21 , 26 , 27 .…”
Section: Discussionsupporting
confidence: 72%
“…After identification of the hernias, they were electively corrected, with patient re-hospitalization and mesh use. No new recurrence was found.There was an isolated case of bile duct injury with partial section of the common bile duct probably due to local chronic inflammation; the conversion to MPLS did not add surgical advantage, which led to the conversion to laparotomy 1 , 13 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This review included 39 studies 64,171e208 with mixed results regarding pain. An analgesic benefit favouring the single port technique was demonstrated in 12 of the studies 64,104,172,183,185,192,195,198,200,202,207,208 ; however, 24 studies 171, 174,176,177,179e182,184,186,187,189e191,193,194,196,197,199,201,203e206 showed no significant difference between the two groups. Three studies 173,175,188 showed an analgesic benefit for the traditional laparoscopic cholecystectomy group.…”
Section: Single Port Surgical Techniquesmentioning
confidence: 87%